The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1103/physrevb.64.214423
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior of certain antiferromagnets with complicated ordering: Four-loopɛ-expansion analysis

Abstract: The critical behavior of a complex N -component order parameter Ginzburg-Landau model with isotropic and cubic interactions describing antiferromagnetic and structural phase transitions in certain crystals with complicated ordering is studied in the framework of the four-loop renormalization group (RG) approach in (4 − ε) dimensions. By using dimensional regularization and the minimal subtraction scheme, the perturbative expansions for RG functions are deduced and resummed by the Borel-Leroy transformation com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
4
17
1
Order By: Relevance
“…First, we focus on the first kink, which approaches the value (∆ φ , ∆ X ) = (0.5, 2) as m → ∞. In [15], it was observed that this limit is compatible with the results in the expansion [3,21,24,25] expanded at large m, where indeed ∆ φ → d−2 2 and ∆ X → 2 up to m −1 corrections. We show here that the m −1 corrections can be computed in a perturbative expansion similar to the usual large N expansion of the O(N ) model (see e.g.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…First, we focus on the first kink, which approaches the value (∆ φ , ∆ X ) = (0.5, 2) as m → ∞. In [15], it was observed that this limit is compatible with the results in the expansion [3,21,24,25] expanded at large m, where indeed ∆ φ → d−2 2 and ∆ X → 2 up to m −1 corrections. We show here that the m −1 corrections can be computed in a perturbative expansion similar to the usual large N expansion of the O(N ) model (see e.g.…”
Section: Introductionsupporting
confidence: 56%
“…While the critical exponents corresponding to the second kink show reasonable agreement, within uncertainties, with the results of [8,19], neither set of values is compatible with the predictions from the expansion, which gives β = 0.370 (5) and ν = 0.715(10) [20,21]. 3 Although it was speculated in [15] that the first kink may be related to the expansion through the large m limit, the results of that study were not sufficient to make any conclusive statements.…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…14 does not correspond to the O 2,2 chiral fixed point. In [39] it was suggested that this kink may correspond to the fully-interacting theory of the expansion analyzed in [71][72][73][74]. To continue our search for the O 2,2 chiral fixed point, we obtain a bound on the dimension of the first scalar operator in the WX representation.…”
Section: Single Correlator In the O(2) × O(2) Casementioning
confidence: 96%
“…[16], with the four-loop ǫ expansion of the so called tetragonal model Ref. [39]. The value of n H (m, 4 − ǫ) coincides with N c /m, where N c is the marginal spin dimensionality of the cubic model obtained in [40], according to the symmetry argument of Refs.…”
mentioning
confidence: 99%